Pengaruh massage terhadap pemulihan kelelahan setelah olahraga lari 800 meter pada Mahasiswa IKOR FIK UNM - Ichsani Ichsani; Andi Atssam Mappanyukki; Muhammad Nurafandi (Seminar Nasional LP2M UNM, 2019)
The aim of the study was to find out whether there was any massage effect on fatigue recovery after 800 meters of running in the IKM FIK UNM students. The population and student samples of IKOR FIK UNM were selected by random sampling with a sample of 10 people. Data analysis techniques used descriptive analysis, normality test and homogeneity test using computer facilities through the SPSS 16 program.  Based on the results of descriptive analysis showed that, from the results of calculations in the data above, obtained t-count of lactic acid before the massage (pretest) and t-count of lactic acid after (posttest) was obtained value of 6.764 with a value of p = 0,000. it turns out that p <0.05; then it can be stated that there is a significant massage effect between lactic acid levels before massage and acid levels after massage (recovery after fatigue) students IKOR FIK UNM. Judging from the mean (average) obtained in the pre-test of 8.70 while the post-test was 6.49, so that there was a decrease in lactic acid levels during recovery after fatigue of 2.21 mg / dl, which means that this answers the research hypothesis that there is a significant massage effect on fatigue recovery after 800 meter running in the IKM FIK UNM students. After physical exercise, the amount of lactic acid in the blood increases, therefore it is necessary to have activities that can accelerate the release of lactic acid so that rapid recovery occurs. Hence in this study can answer the research hypothesis that there is a massage effect on fatigue recovery after 800 mater running activities electricity.